PERCEPTION IN JAINA PHILOSOPHY - Shankar, Uma; Gupta, Sania (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The etymological meaning of the word ‘Pramāṇa’ is ‘Pramiyate anena tat Pramanan’ i.e., valid knowledge is that by means of which something is known. “Pramāṇa is definite valid knowledge of itself and of other things not proved before (PM 1.1)”. Knowledge illuminates itself as well as other objects. In this definition of Pramāṇa all words are significant and have definite purposes to serve. Jaina thinker concerned that they attach more importance to the instrumental meaning as it alone gives us the true meaning of the word ‘Pramāṇa’. Acharya Prabhācandra holds that Pramāṇa may be derived in three ways. In the first place, the auffix ‘Anat’ may be held to be used in active voice meaning i.e., that which knows rightly is Pramāṇa. Here it refers to the nature of a soul which is a knower inherently. From the definition of Pramāṇa as laid down by Manikyanandi it is evident that Pramāṇa is that which gives knowledge of itself and other objects not previously ascertained. This derivation of the word signifies that just as a lamp illumines itself as well as other objects. Secondly, the suffix may be used in the sense of instrumentality. In this sense the word Pramāṇa would mean that by which right knowledge is obtained; just as light shines when obstructions to it are removed, so right knowledge will also illumine when karmic obstructions are partially or totally removed. Thirdly, the word Pramāṇa is used in the Bhāvavaeya where the emphasis of the suffix is on the verb only and the meaning is almost the same as in the active voice. The Sarvārthasiddhī of Pūjyapāda and Tatvārtharajavartika of Akalanka also give all the three senses of the word Pramāṇa and say that it can be understood according to one’s choice in any of three senses mentioned above.